2015
DOI: 10.2337/dc14-1792
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Hemodynamic Response to Incremental Exercise Is Blunted in Poorly Controlled Patients With Uncomplicated Type 1 Diabetes

Abstract: OBJECTIVE Cerebral vasoreactivity to pharmacologically induced hypercapnia is impaired in poorly controlled patients with type 1 diabetes but otherwise free from microangiopathy. However, whether this response is also compromised during exercise, a daily-life physiological condition challenging regional cerebral hemodynamics, is unknown. We aimed to investigate prefrontal cortex hemodynamics during incremental maximal exercise in patients with uncomplicated type 1 diabetes, taking into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Accordingly to a current study, memory-related brain circuits in mPFC were impaired in T2DM (Tagougui et al, 2015) and prefrontal atrophy who had been diagnosed (Lee et al, 2013; Moran et al, 2013). A longitudinal neuropsychological study has convincingly shown that patients with damage to PFC exhibit disorders in the higher cognitive functions (Cohen, 2000).…”
Section: Introductionmentioning
confidence: 71%
“…Accordingly to a current study, memory-related brain circuits in mPFC were impaired in T2DM (Tagougui et al, 2015) and prefrontal atrophy who had been diagnosed (Lee et al, 2013; Moran et al, 2013). A longitudinal neuropsychological study has convincingly shown that patients with damage to PFC exhibit disorders in the higher cognitive functions (Cohen, 2000).…”
Section: Introductionmentioning
confidence: 71%
“…In addition, their study showed a reduced cardiac output, stroke volume and vascular conductance during exercise in these individuals [ 25 ]. Another study in patients with T1D (with inadequate glycaemic control) showed reduced brain O 2 Hb, tHb and HHB (−1.25; −6; −6.5 µM at 90–100% O 2 max) during exercise compared to controls [ 38 ]. In the present study we did not witness beneficial aerobic fitness effects on cerebral hemodynamics (O 2 Hb, tHb and HHB) in T2D, in agreement with our previous study in obese patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of these functions can potentially reduce oxygen delivery and alter neuronal activation and may therefore have detrimental effects on the brain. Indeed, in type 1 diabetes patient total gray matter cerebral blood flow is reduced and regional cerebral hemodynamic response to incremental exercise is blunted compared with control subjects . Furthermore, in animal models of diabetes, improvement of cerebral blood flow by chronic treatment with an angiotensin‐converting enzyme inhibitor (ACE‐inhibitor) was found to be associated with improvement of cognitive function …”
Section: Discussionmentioning
confidence: 99%